Analysis of the impact of social influence on the acceptance of mobile banking applications by consumers in Brazil - Isac, Maria José (2023)
Objective: Analyze the impact of social influence on the acceptance of mobile banking applications. Methodology: A descriptive survey was conducted with 371 users of banking applications over 18 years old. The analysis was performed using the Structural Equation Modeling - Partial Least Square (Smart-PLS 4.0). Originality: This research is a pioneering effort to apply TAM with the inclusion of social influence, in  the COVID-19 pandemic context in Brazil, to analyze the acceptance of mobile banking. Results: The conceptual model has good explanatory power. The research provided empirical evidences that mobile banking adoption is impacted by social influence. This work reinforces the premise that the subject's intention to adopt mobile banking services is influenced by the people who matter to them. In this way, marketing actions/campaigns must consider these reference groups in their strategies in order to promote the technology in question. Contributions: The conceptual model, empirically adjusted and with the corresponding scales, can be used as guidance to application developers and banking marketing management. Due to the lack of empirical researches/studies on the subject in the Brazilian context and the growing use of banking applications, this study expands existing knowledge and provides empirical support for further studies.